TFCP2 Overcomes Senescence by Cooperating With SREBP2 to Activate Cholesterol Synthesis in Pancreatic Cancer - Zhang, Dexiang; Lu, Pinxiang; Zhu, Kaihua; Wu, Haixia; Dai, Yuedi (Frontiers in Oncology, 2021)
KRAS mutation is very common in pancreatic cancer. How pancreatic cancer cells overcome oncogene-induced senescence is not fully understood. Our previous studies showed that up-regulation of TFCP2 (transcription factor CP2) in pancreatic cancer promoted the growth and metastasis of pancreatic cancer cells. However, whether TFCP2 plays an important role in pancreatic cancer cell senescence is not clear. In this study, we found upregulation of TFCP2 expression in pancreatic cancer was associated with KRAS mutation. Overexpression of TFCP2 inhibited cell senescence. Knockdown of TFCP2 promoted cell senescence. Mechanistically, the interaction between TFCP2 and SREBP2 (sterol regulatory element binding transcription factor 2) synergistically activated the expression of HMGCR, a rate-limiting enzyme in cholesterol synthesis, and statins could reverse the inhibitory effect of TFCP2 on senescence. In conclusion, our study reveals a new mechanism underlying the TFCP2 regulation of pancreatic cancer cell senescence, providing a new target for the treatment of pancreatic cancer.